2022
DOI: 10.1186/s12951-022-01443-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction and application of star polycation nanocarrier-based microRNA delivery system in Arabidopsis and maize

Abstract: Background MicroRNA (miRNA) plays vital roles in the regulation of both plant architecture and stress resistance through cleavage or translation inhibition of the target messenger RNAs (mRNAs). However, miRNA-induced gene silencing remains a major challenge in vivo due to the low delivery efficiency and instability of miRNA, thus an efficient and simple method is urgently needed for miRNA transformation. Previous researches have constructed a star polycation (SPc)-mediated transdermal double-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Our previous study showed that the tertiary amines in the side chain of SPc can assemble with the negatively charged nitro groups in TMX through electrostatic interaction, forming the TMX-SPc complex with a particle size of 116 nm (Yan et al, 2021a). The interaction of SPc with nucleic acids is the same as that with TMX, which leads to the formation of a nucleic acid-SPc complex (Li et al, 2019;Li et al, 2022;Yang et al, 2022b). Additionally, the fluorescent dseGFP was appropriate for determining the cellular uptake of an SPc-loaded substance instead of TMX.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that the tertiary amines in the side chain of SPc can assemble with the negatively charged nitro groups in TMX through electrostatic interaction, forming the TMX-SPc complex with a particle size of 116 nm (Yan et al, 2021a). The interaction of SPc with nucleic acids is the same as that with TMX, which leads to the formation of a nucleic acid-SPc complex (Li et al, 2019;Li et al, 2022;Yang et al, 2022b). Additionally, the fluorescent dseGFP was appropriate for determining the cellular uptake of an SPc-loaded substance instead of TMX.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of these two important genes suggested the enhanced delivery of calcium glycinate with the aid of SPc. Our previous studies have demonstrated that the endocytosis-related genes of plants/insects can be activated by SPc application to increase the cellular uptake ( Wang et al., 2021 ; Ma et al., 2022b ; Yang et al., 2022 ). The SPc can also promote the translocation of insect growth regulator/dsRNA across insect cuticle ( Yan et al., 2020 ; Ma et al., 2022a ; Zhang et al., 2022a ; Zhang et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…The SPc-based nano-delivery system can reduce the particle size of synthetic/botanical pesticides and increase their water solubility and dispersity ( Yan et al., 2021b ; Yan et al., 2022 ; Wang et al., 2022b ). At the cellular level, the SPc can activate the clathrin-mediated endocytosis for enhanced cellular uptake and promote the endosomal escape for intracellular spreading of exogenous substances ( Wang et al., 2021 ; Ma et al., 2022b ; Yang et al., 2022 ; Zhang et al., 2022b ). In vivo , the SPc can increase plant uptake to improve the bioactivity of various exogenous substances ( Wang et al., 2022b ; Jiang et al., 2022a ; Jiang et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…With the reduction of dsRNA synthesis cost, Ma et al further applied the spray method in the field trail, and the control efficacy was as good as expectated [ 117 ]. In addition, NPs can also promote the delivery of dsRNA through root tips in Arabidopsis [ 118 ], which is conducive to irrigation and trunk injection development. At present, there are few studies on improving the RNAi efficiency of phytopathogenic fungi by NPs.…”
Section: Co-delivery System In Agricultural Fieldmentioning
confidence: 99%